Pengaruh Disiplin Kerja, Beban Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan pada Indomaret Area Jakarta Barat - Raudatul Jannah; Deden Kurniawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study was conducted with the aim of analyzing the influence of work discipline, workload, and work environment on employee performance, with a focus on Indomaret employees located in the West Jakarta area. The number of samples used in this study was 110 respondents who were directly selected from the employee population, with the data collection technique through the distribution of questionnaires using a Likert scale. The collected data were then analyzed using the multiple linear regression method with the help of SPSS software version 30. The results of the study indicate that partially, the variables of work discipline, workload, and work environment are proven to have an influence on employee performance, where each factor makes a different contribution in supporting or hindering work productivity. Meanwhile, simultaneously, the three independent variables are proven to have a significant influence on the dependent variable, namely employee performance. This finding confirms that the combination of good work discipline factors, balanced workload management, and a conducive work environment is very important in creating sustainable performance improvements. Thus, this study is expected to provide practical contributions as input for Indomaret management in the West Jakarta area in designing more effective human resource management strategies, both through policies to improve discipline, proportional workload management, and the creation of a work environment that is more supportive of employee comfort and motivation.